Implementasi Peran Kodim 1605/Belu dalam Mengelola Potensi Wilayah Pertahanan Perbatasan Darat Nusa Tenggara Timur - Timor Leste - Widiyatmoko Widiyatmoko; Deni Dadang AR; Dwi Hartono (AKADEMIK: Jurnal Mahasiswa Humanis, 2026)
This study addresses the gap between the normative role of district military commands (Kodim) within Indonesia’s universal defense system and the persistent socio-economic and security challenges in land border areas. Border regions such as Belu-Malaka continue to face underdevelopment, poverty, and non-traditional threats, which potentially weaken territorial resilience. The research aims to analyze how Kodim 1605/Belu implements its role in managing territorial potential to strengthen border defense and community resilience along the Indonesia-Timor Leste land border. A qualitative case study approach was employed, with data collected through in-depth interviews with military personnel, local government officials, and community leaders, complemented by field observations and document analysis. Data were analyzed using an interactive model involving data reduction, thematic categorization, and contextual interpretation. The findings indicate that Kodim 1605/Belu has played a constructive role through integrated territorial development programs, including infrastructure support, community empowerment, and the cultivation of national defense awareness. These efforts have contributed to social cohesion and early threat detection at the community level. However, structural constraints such as limited resources, coordination gaps with civilian agencies, and geographical challenges remain significant. Strengthening inter-agency synergy and institutional integration is therefore essential to ensure the sustainability and effectiveness of territorial defense management in border areas.